Challenge Accepted! a Critical Reflection on How to Perform a Health Survey Among University Students-An Example of the Healthy Campus Mainz Project - Jennifer L. Reichel; Thomas Rigotti; Thomas Rigotti; Ana Nanette Tibubos; Antonia M. Werner; Markus Schäfer; Dennis Edelmann; Daniel Pfirrmann; Nicole Deci; Manfred E. Beutel; Birgit Stark; Perikles Simon; et al. (Frontiers Media S.A., 2021)
Background: Universities represent an important setting of everyday life for health promotion. The Healthy Campus Mainz project aims to develop an evidence-based and comprehensive student health management program covering physical, mental, and social health promotion. Hence, an initial health survey was performed in order to identify the students' health concerns and resources. Up until now, it remains unclear which topics to choose in a health survey among university students and which strategies can be recommended to receive an acceptable response rate or representative student sample within a university setting. The present paper contributes to the call for the present research topic "Public Health Promotion in University Students" by describing methods for health assessment. Therefore, the current paper aims to give an empirical example on how to perform a health survey among university students, focusing on (1) choosing topics for the survey and (2) methodological considerations of how to reach the target population.Methods: An online questionnaire including around 270 items was developed covering a comprehensive set of health topics. Participants were recruited via the university email. Mixed channels for survey promotion, such as lecture visits and social media, were used, accompanied by different monetary and non-monetary incentives. Descriptive analyses were performed to describe the sample.Results: A total of 5,006 participants (out of 31,213 registered students) viewed the first page of the questionnaire; of whom, 4,714 continued further. After a manual data cleaning according to the predefined criteria, the final sample was 4,351, demonstrating a response rate of 13.9%. Students from different study disciplines participated. However, some study disciplines showed a low participation rate, hence, making the results not free from some bias.Discussion: This survey is exceptional as it integrates a great variety of health aspects. The incentive strategy demonstrated promising results. Future research should try to improve target-group-specific recruitment strategies for the traditionally underrepresented groups, such as males and specific study disciplines. This would not only include advancing marketing strategies, but also refining the incentive strategy.